ANALISIS PEMBELAJARAN KETERAMPILAN DASAR PRAKTIK KLINIK - Ekawati (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
The objectives of the research are to determine: (1) How the implementation of clinical practicebasic skills learning, (2) How the cooperation arrangement between STIKES A. Yani with partners, (3) How the achievement of students, (4) constraints encountered in implementation of clinical practice learning basic skills. This research was conducted in STIKES A. Yani Yogyakarta for one month using qualitative research methods using case study and descriptive design. Subjects in this study are students who take the course Basic Skills Practice Clinic in the second semester, practice coordinator, Clinical Instructure, Diklat. Conclusions: (1) The practice of basic skills practice is already carried out in accordance with apredetermined schedule, and for setting a schedule determined by the practice field, (2) STIKESA. Yani Yogyakarta in cooperation with other institutions are always stated in the MOU, the practice of land Krikteri hospitals or public hospitals are type A / B / C, and health centers topractice basic skills practice, (3) Of the 296 students who carry out the practice of clinical practicebasic skills , Students who get an A as many as 72 people (24.32%) and the value of B shares of224 students (75.68%). Student achievement is also influenced by the level of their own confidence in doing a land perasat in practice, (4)  The constraints faced in the course of practice the basic skills of clinical practice is bimbingan lecturers less intensive supervision, the practice ofland cases so that student achievement is less. Keywords: Learning, Basic Skills Practice Clinic.